Experimental and numerical study of heterogeneous pressure-temperature-induced lethal and sublethal injury of lactococcus lactis in a medium scale high-pressure autoclave - Kilimann, Klaus Valentin; Kitsubun, Panit; Delgado, Antonio; Gänzle, Michael Gerhard; Chapleau, Nicolas; Le Bail, Alain; Hartmann, Christoph (Biotechnology and Bioengineering, 2006)
The present contribution is dedicated to experimental and theoretical assessment of microbiological process heterogeneities of the high-pressure (HP) inactivation of Lactococcus lactis ssp. cremoris MG 1363. The inactivation kinetics are determined in dependence of pressure, process time, temperature and absence or presence of co-solutes in the buffer system namely 4 M sodium chloride and 1.5 M sucrose. The kinetic analysis is carried out in a 0.1-L autoclave in order to minimise thermal and convective effects. Upon these data, a deterministic inactivation model is formulated with the logistic equation. Its independent variables represent the counts of viable cells (viable but injured) and of the stress-resistant cells (viable and not injured). This model is then coupled to a thermo-fluiddynamical simulation method, high-pressure computer fluid dynamics technique (HP-CFD), which yields spatiotemporal temperature and flow fields occurring during the HP application inside any considered autoclave. Besides the thermo-fluiddynamic quantities, the coupled model predicts also the spatio-temporal distribution of both viable (VC) and stress-resistant cell counts (SRC). In order to assess the process non-uniformity of the microbial inactivation in a 3.3-L autoclave experimentally, microbial samples are placed at two distinct locations and are exposed to various process conditions. It can be shown with both, experimental and theoretical models that thermal heterogeneities induce process non-uniformities of more than one decimal power in the counts of the viable cells at the end of the treatment. © 2006 Wiley Periodicals, Inc.
UnivIS-Import:2015-03-09:Pub.2006.tech.ITC.stmmec.experi_8
Keywords: Bacterial inactivation; Baroprotection; High-pressure temperature processing; Non-uniform cell death; Predictive modelling